Activation of cholinergic anti-inflammatory pathway involved in therapeutic actions of α-mangostin on lipopolysaccharide-induced acute lung injury in rats. (September 2020) - Yang, Zhe; Yin, Qin; Olatunji, Opeyemi Joshua; Li, Yan; Pan, Shu; Wang, Dan-dan; Zuo, Jian
Introduction: Alpha-mangostin (MAN) possesses a wide variety of pharmacological effects. In this study, we investigated its effect on cholinergic anti-inflammatory pathway (CAP), and tested if CAP regulation was involved in the therapeutic action on acute lung injury (ALI). Methods: Male Sprague Dawley rats were pre-treated with MAN (40 mg/kg) for 3 days and ALI was induced with an intraperitoneal injection of lipopolysaccharide (LPS). Certain rats received monolateral vagotomy or sham surgery. The effects on inflammatory reactions and relevant pathways in ALI rats or LPS pre-treated RAW 264.7 cells were investigated by histological, immunohistochemical, immunoblotting, RT-qPCR, and immunofluorescence assays, while levels of proinflammatory cytokines, acetylcholine (Ach) and the enzymatic activity of acetylcholinesterase (AchE) were determined by corresponding quantitative kits. Results: Oral administration of MAN reduced the severity of ALI, while vagotomy surgery antagonized this effect. MAN restored the decline in α7 nicotinic acetylcholine receptor (α7nAchR) in the lungs of ALI rats, and promoted the expression of α7nAchR and choline acetyltransferase (CHAT) in RAW 264.7 cells. Although AchE expression was barely affected by MAN at 5 μg/ml, its catalytic activity was reduced by almost 95%. Extracellular rather than intracellular Ach was notably raised shortly after MAN treatment. Furthermore, MAN at 5 μg/ml effectively inhibited LPS-induced increase in phosphorylation and nucleus translocation of p65 subunit, and secretion of TNF-α and IL-1β, which was then offset by methyllycaconitine citrate hydrate. Conclusion: MAN activated CAP by increasing peripheral Ach and up-regulating α7nAchR expression, which eventually led to NF-κB inhibition and remission of acute inflammations.